Steroid Induced Glaucoma and Primary Angle Closure Glaucoma: A Case Report of Mixed Mechanism Glaucoma: Poster Presentation - Case Report - Resident - Masloman, Anugrah Handini; Kasih, Franky (Majalah Oftalmologi Indonesia, 2023)
Introduction : Steroid induced glaucoma is a form of secondary open angle glaucoma (OAG) caused by adverse effects of steroid usage. Primary angle closure glaucoma (PACG) is characterized by shallow anterior chamber accompanied by peripheral anterior synechiae (PAS), elevated IOP and glaucomatous optic neuropathy (GON). Case Illustration : A 58 year-old woman presented with red eye, blurry vision, pain in her right eye radiating to the head, watery eye and halo. History of experiencing recurrent red eye, improving after taking steroid topical drug for about 3 months. Visual acuity 6/20 ph 6/20, IOP 39 mmHg, mixed conjunctival injection, shallow anterior chamber Van Herick 1-2, dilated pupil and iris pigment on anterior capsule of lens. Posterior segment showed glaucomatous optic neuropathy with cup disc ratio 0.8-0.9, anterior chamber depth 2.58, and thinning of optic nerve head layer. Patient was diagnosed with steroid induced glaucoma and mixed mechanism PACG. The patient underwent trabeculectomy procedure after mannitol injection was given to reduce IOP. Discussion : We diagnosed the patient with steroid induced glaucoma and mixed mechanism PACG based on history, clinical findings, and diagnostics. Steroid raised IOP by accumulating polymerized glycosaminoglycans (GAGs) in the trabecular meshwork, producing "biologic edema" thus increased outflow resistance. PACG was determined based on Van Herick and anterior chamber depth. Trabeculectomy remains an effective treatment in this case where medications were failed to control IOP. Conclusion : Steroid induced glaucoma commonly found in OAG, definitive treatment includes halting steroid drugs and trabeculectomy. Further follow-up is needed to evaluate angle closure mechanism.